Remanufacturing : when does it make sense to consider this as a viable option - Lee, Yi Wei (2016)
Remanufacturing is the process of returning end-of-life products to a good-as-new status with warranty provided. It is increasingly becoming a viable option to venture into to meet the global targets set on emission, but its benefits are not made aware to as many. This report aims to raise the awareness on the benefits of remanufacturing by studying key industry leaders and their successful driving factors and provide a comprehensive checklist to help companies decide on when it makes sense to consider remanufacturing as a viable business option. The cost model findings show that while remanufacturing would definitely result in higher profits, several other intangible factors need to be present in order to drive a successful remanufacturing business model, but it still faces several legislation problems that need to be overcome.